2021
DOI: 10.3389/fcell.2020.613540
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs Dysregulated in Juvenile Myelomonocytic Leukemia: CircMCTP1 Stands Out

Abstract: Juvenile myelomonocytic leukemia (JMML), a rare myelodysplastic/myeloproliferative neoplasm of early childhood, is characterized by clonal growth of RAS signaling addicted stem cells. JMML subtypes are defined by specific RAS pathway mutations and display distinct gene, microRNA (miRNA) and long non-coding RNA expression profiles. Here we zoom in on circular RNAs (circRNAs), molecules that, when abnormally expressed, may participate in malignant deviation of cellular processes. CirComPara software was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…We verified that running CircIMPACT with the k-means option for sample separation, circHIPK3 remains in the top 25. In accordance with Li et al [24], among the differentially expressed circRNAs, CircIM-PACT identified circHIPK3, which is downregulated in the automatically defined group (g1), corresponding to bladder cancer samples (Figure 3B). Different circRNAs can separate sample groups in different ways, according to the experimental design, the dataset type and structure.…”
Section: Case Study: An Exploration Of Gene Expression and Pathways Impacted By Circrna In Bladder Cancersupporting
confidence: 87%
See 3 more Smart Citations
“…We verified that running CircIMPACT with the k-means option for sample separation, circHIPK3 remains in the top 25. In accordance with Li et al [24], among the differentially expressed circRNAs, CircIM-PACT identified circHIPK3, which is downregulated in the automatically defined group (g1), corresponding to bladder cancer samples (Figure 3B). Different circRNAs can separate sample groups in different ways, according to the experimental design, the dataset type and structure.…”
Section: Case Study: An Exploration Of Gene Expression and Pathways Impacted By Circrna In Bladder Cancersupporting
confidence: 87%
“…To demonstrate CircIMPACT functions and potential we conducted a sample analysis using bladder cancer and matched control tissue data. CircIMPACT analysis identified HPSE dysregulation according to circHIPK3 expression reduction in bladder cancer, in line with the non-canonical regulatory axis previously proven and linked to the disease [ 24 ]. In our sample analysis, the software was applied to a relatively small and simple dataset.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…These peculiar RNAs regulate several biological processes with different mechanisms. Moreover, circRNAs are emerging as key oncogenic or tumour suppressor molecules whose expression is dysregulated in disease, cancer and when genomic translocations occur [4][5][6]. They represent stable diagnostic and prognostic markers [7,8].…”
Section: Introductionmentioning
confidence: 99%